Pengembangan Bahan Ajar Bangun Ruang Menggunakan Model RME Terhadap Motivasi Belajar Siswa Kelas IV SD - Ahmad Landong; Mayang Pratiwi Sembiring; Nurazlaila Safika; Siti Nurjannah (Jurnal Dirosah Islamiyah, 2023)
This research aims to design an existing material into a new material format with the aim of creating teaching and learning activities that are more active, interesting and meaningful than before, and do not conflict with the curriculum. The type of research used is Research and Development (R&D) using the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. However, in this study researchers only implemented the ADDIE development model only up to the Development stage. This study aims to produce student teaching materials using the Realistic Mathematic Education (RME) model that can increase student learning motivation. This research was conducted at SDN 101798, Deli Tua sub-district. The subjects of this research were experts from lecturers and teachers as well as grade IV students of SDN 101798 Deli Tua. The object of this research is teaching materials for building space using the RME model. The results of the research include validation 1 with material experts obtaining a score of 71.2 with decent criteria. Furthermore, validation 2 by material experts obtained a score of 81.6 with very feasible criteria. The results of validation with teaching material experts at stage 1 obtained a score of 69.6 with decent criteria and at stage 2 validation with teaching material experts obtained a score of 85.6 with a very feasible category. The results of validation by learning experts or teachers obtained a score of 92.6 with very feasible criteria. From the scores obtained from the three experts, it can be said that the teaching materials for building space using the Ralistic Mathematics Education (RME) model developed can be used in the learning process. This shows that The developed teaching materials have an impact on the learning motivation of grade IV students. Keywords: Keywords: Teaching Materials for Building Space Keywords: RME Learning Model Keywords: Motivation Student Learning